2004
DOI: 10.1007/s10350-003-0115-5
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Colorectal Cancer Registries in the United States

Abstract: The United States is underserved by registries for inherited colorectal cancer, having enrolled only a small proportion of the families theoretically available. Registries differ in fundamental aspects of function. More collaboration and more registries are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…2,3 The development of many Polyposis Registries around the world helped to spread the importance of screening, prophylactic colectomy, and surveillance strategy translating into better prognosis. 6 This fact is clearly reflected in the CRC incidence reported in countries with regular surveillance, where figures of 50-70% and 3-10% are, respectively, found among symptomatic probands and screened patients. 14,15 Furthermore, survival advantages have been registered, with death occurring in 10 of the 120 call-up patients (8.3%) and 58 of the 116 probands (50%).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…2,3 The development of many Polyposis Registries around the world helped to spread the importance of screening, prophylactic colectomy, and surveillance strategy translating into better prognosis. 6 This fact is clearly reflected in the CRC incidence reported in countries with regular surveillance, where figures of 50-70% and 3-10% are, respectively, found among symptomatic probands and screened patients. 14,15 Furthermore, survival advantages have been registered, with death occurring in 10 of the 120 call-up patients (8.3%) and 58 of the 116 probands (50%).…”
Section: Discussionmentioning
confidence: 87%
“…Cuthbert Dukes and J.P. Lockhart-Mummery through the foundation of the first Polyposis Registry in St. Mark's Hospital in 1924, 4 many Polyposis Registries have been established in many countries, leading to a decrease in CRC prevalence and improved life expectancy. 5,6 Since the classical papers from Gardner 7 and Crail 8 describing Gardner and Turcot syndromes, much knowledge has been accumulated regarding the importance of extracolonic manifestations (ECM) of the disease. Today, it is well recognized that FAP is a complex systemic disorder that may affect tissues from ectodermal, endodermal, and mesodermal germ layers.…”
Section: Introductionmentioning
confidence: 99%
“…Services include medical evaluation, risk assessment, and genetic counseling. A recent survey by Church et al 18 found 18 registries in the United States. To our knowledge, just six registries are operational in South America (2 in Argentina, 2 in Brazil, 1 in Uruguay, and 1 in Chile).…”
Section: Discussionmentioning
confidence: 98%
“…In those with two or more relatives with CRC, a threefold increased risk exists, and among those with a relative with early onset CRC, the risk of developing CRC is even higher [3][4][5][6]. The known familial cancer syndromes are hereditary nonpolyposis colorectal cancer (HNPCC; also called Lynch syndrome), seen in 1-3% of patients with CRC [2,7,8] familial adenomatous polyposis coli (FAP) seen in less than 0.1% [9,10] and, the very rare juvenile polyposis and PeutzJehger's syndromes [11]. Depending on the penetrance of the gene carrier, patients with these syndromes will develop CRC at a young age.…”
Section: Introductionmentioning
confidence: 99%